A theory of venturing: A critical realist explanation of why my father is not like Richard Branson. (September 2019) - Galloway, Laura; Kapasi, Isla; Wimalasena, Lakshman
This article presents a theory of venturing using a critical realist approach. Venturing is presented as an outcome of reflexive engagement between individuals and circumstances, where opportunity is perceived in relation to some idiosyncratically defined value. Traditionally, venturing has been considered as necessarily involving financial value orientation. Removing the primacy of financial ambitions affords better explanation of real-life business activity. Venturing is presented also as temporally informed and informing through a lifetime, and thus it influences ongoing work choices, including further venturing. The benefits to theory and practice are outlined, including informing support of disparate venturing and of entrepreneurship as a specific type.